RESISTENSI Klebsiella sp TERHADAP MEROPENEM DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Afifah Afifah; Tunggul Adi Purwonegoro; IDSAP Peramiarti (Scripta Biologica, 2017)
Resistant Gram-negative bacteria, particularly Klebsiella sp., has become a serious problem in hospitals as one of the main causes of nosocomial infections spread through urine catheterization. Infections of Klebsiella sp. producing extended-spectrum beta-lactamase (ESBL) can lead to significant economic and clinical negative outcome. This study was aimed to determine the sensitivity of ESBL Klebsiella sp. against meropenem as a cause of nosocomial infections in Prof. Dr. Margono Soekarjo hospital. This research obtained urine samples from the urinary catheter of patients hospitalized for at least two days in the surgical ward and intensive care unit. ESBL examination conducted by the initial screen test, meanwhile, sensitivity test to meropenem done by using disk diffusion test. Among the 40 patients examined in this study 7.5% isolates were Klebsiella sp-positive. This research identified five percent of the total patients as ESBL positive with the level of sensitivity against meropenem was revealed as resistant.